ASPECT TOXICOLOGIQUE ET PHYSICOCHIMIQUE DU 1,5-DIPENTANAL - Mohammed, Bouzid; Boudjemaa, Bezzazi; Amina, Djadi; Hamid, Ait Amar; Ahmed, Ghouini (European Scientific Journal, ESJ, 2014)
The 1,5-dipentanal is an important organic molecule: pedagogically, the molecule provides a range of interesting chemical reactions (Aldolisation, Michael, glycolysis, Cannizzaro, Mannich ...). It has the same reaction mechanisms for teaching the fundamentals of ecotoxicology in particular and chemistry in the environment in general. The extent of these applications between the fine disciplines (medical sciences, pharmacological chemistry, enzyme technology, technology of biological membranes and tissues, cytochemistry, histochemistry, immunochemistry, microscopy, X-ray ...) generates a rich multidisciplinary education first. Glutaraldehyde reacts with proteins, sugars and lipids feature free groups (-NH2). The amine group (NH2) reacts with the nucleophilic carbonyl electrophilic aldehyde (- CHO). The consequences of this mechanism in vivo are at the heart important pathophysiological (diabetes, renal failure, ...). Moreover, the miscibility with water (100%), high reactivity in physiological, highly evaporable terms (air contamination), chemical intermediate in industry and a must for all disinfection and sterilization of equipment. A good compromise between advantage and disadvantage impose a regulated management of the molecule as effluent or residue. It can not be rejected in sanitation, or natural mitan. The development of processes requested by the practical interest of the molecule and its management as harmful liquid waste is required.